Retropseudogenes constitute the major part of the human elongation factor 1 alpha gene family. - Madsen, H O (1990)
The elongation factor 1 alpha (EF-1 alpha) is a protein which promotes the GTP-dependent binding of aminoacyl-tRNA to ribosomes in the protein synthesis process. A human gene coding for EF-1 alpha has previously been cloned and sequenced along with a pseudo-gene. Here, we have further analyzed the family of human EF-1 alpha genes. Using an EF-1 alpha cDNA as probe twelve genomic EF-1 alpha-like clones were isolated and analyzed. Four of these were sequenced and found to contain EF-1 alpha retropseudogenes. A Southern blot analysis indicated that the remaining eight clones also contained retropseudogenes. Genomic Southern blot analysis revealed at least twenty loci in the human genome with sequence homology to the EF-1 alpha cDNA. Besides the already described active gene only one potentially active locus was found. The others appeared to be retropseudogenes. EF-1 alpha retropseudogenes were also found to be abundant in the mammalian species mouse and pig, while the chicken contained only one presumably active EF-1 alpha gene.